If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -1cy + 8 = 8 + -5y + -12 Reorder the terms: 8 + -1cy + -2y = 8 + -5y + -12 Reorder the terms: 8 + -1cy + -2y = 8 + -12 + -5y Combine like terms: 8 + -12 = -4 8 + -1cy + -2y = -4 + -5y Solving 8 + -1cy + -2y = -4 + -5y Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -1cy + -8 + -2y = -4 + -8 + -5y Reorder the terms: 8 + -8 + -1cy + -2y = -4 + -8 + -5y Combine like terms: 8 + -8 = 0 0 + -1cy + -2y = -4 + -8 + -5y -1cy + -2y = -4 + -8 + -5y Combine like terms: -4 + -8 = -12 -1cy + -2y = -12 + -5y Add '2y' to each side of the equation. -1cy + -2y + 2y = -12 + -5y + 2y Combine like terms: -2y + 2y = 0 -1cy + 0 = -12 + -5y + 2y -1cy = -12 + -5y + 2y Combine like terms: -5y + 2y = -3y -1cy = -12 + -3y Divide each side by '-1y'. c = 12y-1 + 3 Simplifying c = 12y-1 + 3 Reorder the terms: c = 3 + 12y-1
| 200x+56-87x= | | 12x+8y=36 | | -76=19s-38 | | 8t-3=21 | | 18=15-z | | 49-3m=4m+4 | | 2(4x+9)=-17+19 | | 3y+40=7y-10 | | 8y=78 | | 2x=20-10 | | x^2-32+256=0 | | 2x-13=10x+11 | | 30=3h+18-2(h-3) | | 38=6(1[w+4]1)-8w | | 3.1y=11.47 | | 5s^2-35s+60=0 | | 4(2y-1)+3=3x-1 | | 5+66x=44x+17 | | 6-3[2-(2y-2)]= | | 8p+6=15+7p | | -x-10x+4=0 | | -4(3x-7)+2(y-4x+3)= | | 10x-8=9x+5 | | abc=123 | | 6r-3=-2r+-2 | | 15r^3+6r^2-60r= | | 3x-9+4x=8x+12 | | -2y+5=-5y | | -16x^2+67x+10=36 | | 5-5*62= | | 8x^2(-3x^2+9x-2)= | | -7x-10=-8-5x |